On Body and Technologies in a Technical University - Kačerauskas, Tomas (Problemos, 2008)
The article reviews the conference Body and Technologies. The author raises the questions about the role of philosophy both in the society in general and in the universities in special. According to the author, the interdisciplinary research should not be a pretext to decrease the high professional demands. The author discusses the motivations of the escape from philosophy both to the broader (to so called social sciences) and to the narrower (to comparative studies, deconstruction, analytics) space. The question is raised if this escape doesn't mean a decrease of philosophical responsibility. The author raises such criterions of sciences as simplicity and economy of auxiliary means. According to the author, the scientific conferences collect the Lithuanian philosophers in order to care about both their community and the situation of philosophy in the universities and institutes. The question is raised what role of a technical university is in the development of philosophical ideas.